METHODS OF FORMING A CULTURE FOCUSED ON CREATIVITY IN FUTURE TEACHERS - Nagmetova Nursulu Muratbaevna (Web of Journals Publishing, 2026)
The effectiveness of a teacher's professional development in today's world is determined by their ability to adapt quickly to a dynamic educational environment, as well as their willingness to modify the methodological, content-related and general pedagogical components of their work in line with the current demands of society. The fundamental predictors of a teacher's professional development have been identified as developed intelligence and a high level of creativity.
Keywords: Creativity, education, pedagogy, creativity, pedagogical activity.